Recurrent acute myocardial infarction associated with calcified pseudoaneurysm: A case analysis - Zhi-Ling Gao; Ping Xie; Xing Zhou; Yan-Ling Li (Journal of International Medical Research)
Left ventricular pseudoaneurysm (LVP), a rare but life-threatening complication following acute myocardial infarction (AMI), has an incidence of approximately 0.5% and a high mortality rate due to its significant risk of rupture. Early detection and timely surgical intervention are crucial. The diagnosis of LVP can be effectively achieved through various imaging modalities, including transthoracic echocardiography, cardiac magnetic resonance imaging, computed tomography angiography, and left ventriculography. However, determining the optimal therapeutic strategy requires a comprehensive multidisciplinary discussion approach and individualized consideration. This report presents a challenging case of a patient who experienced recurrent AMI 25 years after the initial event, with an incidental discovery of a calcified LVP. The distinctive features of this case include the long-term presence of a calcified pseudoaneurysm without rupture and the successful management strategy employed following the recurrent AMI.